Effect of Moringa (Moringa oleifera) Pulp Incorporation on Sensory Parameters and Textural Qualities of Fresh Shrikhand - Kumar, S. Sharath; Swathi, S.; Swarnalatha, G.; Kartikeyan, S.; Punitha, K. (International Journal of Bio-resource and Stress Management, 2025)
The study was conducted at Dept. of Dairy Technology, College of dairy science and food technology, Raipur, Chhattisgarh, India during March, 2024 to July, 2024 to evaluate the effect of moringa pulp incorporation on sensory parameters and textural qualities of fresh shrikhand. Fermented milk products are an integral part of the human diet in many regions of the world. Shrikhand is one of the important fermented milk products. Moringa oleifera commonly known as the drumstick tree. Every part of the Moringa tree, including the fruits or pods, flowers, seeds, stem, and roots, holds significant importance for human health and nutrition. This study was aimed to conduct develop to add value for Shrikhand by blending Moringa pulp and evaluate the sensory and textural qualities of Shrikhand. A control (0%) and 4 lots of Moringa pulp blended Shrikhand samples (5,10,15 and 20 percent) were prepared. The fresh Shrikhand samples were evaluated for its sensorial and textural quality parameters. Moringa pulp blending had significant (p<0.05) effect on sensory attributes of fresh Shrikhand samples, the color and appearance, consistency, flavor and taste, sweetness and overall acceptability scores. However T0, T1 and T3 samples were on par in color and appearance, flavor and taste, sweetness and overall acceptability. Moring pulp blending had significant (p<0.05) effect on the textural qualities of fresh Shrikhand samples. T0 sample was secured highest values of firmness (12668.57), stickiness (10056.28), spreadability (12706.61) and Adhesiveness (3856.39), whereas T4 sample was secured lowest values of firmness (6650), stickiness (5409.46), spreadability (7571.64) and Adhesiveness (1317.33) respectively.